2009
DOI: 10.1007/s11432-009-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Power allocation for non-orthogonal decode-and-forward cooperation protocol

Abstract: This paper studies the power allocation problem for the non-orthogonal decode-and-forward (NDF) cooperation protocol with selection relaying. With the availability of the magnitudes of all channel gains at the source, the power allocation is explored that maximizes the mutual information between the source and destination subject to a total power constraint. The minimum power that avoids the outage of the relay is set as a condition, under which the power allocation problem becomes one of selecting the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Optimal power allocation in AF networks has been studied in [7,8]. Most of these solve for the optimal power division between the source and relay nodes to maximize capacity or minimize outage probability.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal power allocation in AF networks has been studied in [7,8]. Most of these solve for the optimal power division between the source and relay nodes to maximize capacity or minimize outage probability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as equal power allocation (EPA) was used for the local and relayed data, power resource was inefficiently utilized. It has been shown that optimal power allocation (OPA) algorithm could be devised to improve outage probability [9], capacity [10,11], symbol error rate (SER) [12] and pairwise error probability (PEP) [13] performance of cooperative systems Nevertheless, OPA algorithm for a particular cooperative system remains an open issue.…”
Section: Introductionmentioning
confidence: 99%